A comparison of association methods for cytotoxicity mapping in pharmacogenomics - Brown, Chad; Havener, Tammy; Everitt, Lorraine; McLeod, Howard; Motsinger-Reif, Alison (Frontiers in Genetics, 2011)
Cytotoxicity assays of immortalized lymphoblastoid cell lines (LCLs) represent a promising new in vitro approach in pharmacogenomics research. However, previous studies employ- ing LCLs in gene mapping have used simple association methods, which may not adequately capture the true differences in nonlinear response profiles between genotypes. Two common approaches summarize each dose-response curve with either the IC50 or the slope parameter estimates from a hill slope fit and treat these estimates as the response in a linear model. The current study investigates these two methods, as well as four novel methods, and compares their power to detect differences between the response profiles of genotypes under a variety of different alternatives. The four novel methods include two methods that summarize each dose-response by its area under the curve, one method based off of an analysis of variance (ANOVA) design and one method that compares hill slope fits for all individuals of each geno- type. The power of each method was found to depend not only on the choice of alternative, but also on the choice for the set of dosages used in cytotoxicity measurements. The ANOVA- based method was found to be the most robust across alternatives and dosage sets for power in detecting differences between genotypes.